Public Policy Implementation in Efforts to Improve Public Service Quality in Tangerang City - Syamsul Bahri; Khasan Effendy; Ngadisah; Sampara Lukman (GoAcademica Research & Publishing, 2020)
Public service is the most critical task for the Tangerang City government bureaucracy. The Tangerang City Government is the government organ closest to the people it serves to empower. This study seeks to describe the implementation of public policies to improve the quality of public services to improve people's welfare in the city of Tangerang. This research uses a qualitative approach with descriptive methods. The results show that public services to improve welfare can be seen from 5 dimensions, namely: (1) Tangibles are something that is visible and directly proven, generally aimed at the form of office appearance, the comfort of the room where it provides public services, the completeness of the facilities provided, the presence of officers who serve to support implementation of public services; (2) Reliability, which is the ability to deliver promised public services in a timely manner, according to procedures, equality / equal treatment of officers with simplicity, and speed, is a reliable, accurate and consistent capability in providing public services as desired by consumers (3) Responsiveness is a high sensitivity towards consumers followed by acting appropriately in accordance with the needs as seen by the desires of public service providers to help consumers; (4) Assurance as a guarantee of security in obtaining public services so that there are no doubts about the emergence of errors in the provision of public services; (5) Emphaty, namely feeling what other people think and trying to understand and understand what the wants, wants and needs of customers include; understanding customer needs, desires (motivation) to help customers (society), conformity of service to customer needs (community), concern for customers (community), and the desire to follow up on criticism and suggestions with problems managing the needs of service users.